Anaplasma phagocytophilum in White-tailed Deer - Massung, Robert F. (Centers for Disease Control and Prevention, 2005)
We examined the reservoir potential of white-tailed deer for Anaplasma phagocytophilum. Results suggest that white-tailed deer harbor a variant strain not associated with human infection, but contrary to published reports, white-tailed deer are not a reservoir for strains that cause human disease. These results will affect surveillance studies of vector and reservoir populations.